Diagnostic journey and genetic analysis of a novel homozygous CYP2U1 mutation causing autosomal recessive spastic paraplegia type 56 (SPG56) in a consanguineous family - Hong-ping Yu; Jing Zou; Xiang Chen; Ying Chen; Dan-dan Ruan; Qian Chen; Jian-hui Zhang; Qiong Cheng; Xing-lin Ruan; Wei Wen; Li Chen; Jie-wei Luo; et al. (BMC Neurology)
Abstract Hereditary spastic paraplegia (HSP) is a neurodegenerative disorder, with spastic paraplegia type 56 (SPG56) being an exceptionally rare, autosomal recessive subtype caused by mutations in the CYP2U1 gene. This study reports a complex case of an adult female from a consanguineous family who presented with cognitive developmental delays, short stature, and progressive neurological symptoms. At age 39, she developed unilateral tremors, which progressed to generalized tremors and leg weakness with a tiptoe gait. The clinical findings included hypertonia in the upper limbs, exaggerated reflexes in the lower limbs, vague speech, and emotional disturbances. Brain MRI revealed corpus callosum thinning, “ears of the Lynx” sign, bilateral globus pallidus calcifications, and mild brain atrophy. Comprehensive genomic analysis, including whole exome sequencing (WES), copy number variation (CNV) assessment, mitochondrial DNA sequencing, variant filtering, and Sanger sequencing, identified a homozygous c.913 C > T (p.His305Tyr) mutation in CYP2U1 (NM_183075). The heterozygous carriers presented no symptoms. This case contributes to the phenotypic spectrum of SPG56, offering new insights into its diagnosis and genetic underpinnings.